The 8 habit : from effectiveness to greatness - Covey, Stephen R. (London : Simon & Schuster, 2007)
That the world has changed and is continuing to change at a rapid pace is not news. People are much more aware of everything around them. The consumer revolution has accelerated dramatically. But something vital is missing in all of this change. Leadership has not kept up with the changes going on in the world. From board rooms to classrooms, leadership is being challenged on a daily basis yet no new leadership model has been given. In this new, important work, bestselling author Stephen R. Covey offers ideas of how leadership roles have changed and how one can take on the roles of the new leader. Dr. Covey introduces the 4 roles of the new leader -- modelling, pathfinding, aligning and empowering -- and how those qualities can change you and your organization. He discusses how trust can be lost throughout organizations and how it is imperative that any organization bring trust back to the company if it is to survive. Covey also shows how to go from what he calls a "want to" person to a "can do" person and how doing so can completely transform people and organizations.
Includes index.
Keywords: Leadership; Success; Self-actualization (Psychology).